Physicochemical characteristics and biological activities of grape polysaccharides collected from different cultivars. (January 2023) - Leng, Xiangpeng; Miao, Wenjun; Li, Jizhen; Liu, Yuanxia; Zhao, wenwen; Mu, Qian; Li, Qiu
Graphical abstract: The polysaccharides from BC and BF grapes showed a protective effect against myocardial I/R injury in mice. Highlights: Polysaccharides are extracted from four grape varieties by ultrasonic-assisted extraction. Four grape polysaccharides had similar structural characteristics but different antioxidant activities. 'Beichun' (BC) and 'Benni fuji' (BF) polysaccharides possessed a better protective effect against myocardial I/R injury in mice. Abstract: In this study, four wine grape polysaccharides were extracted and optimized by using an efficient ultrasound-assisted extraction. A three-level, three-factor Box Behnken Design (BBD) combining with response surface methodology (RSM) was employed to optimize the extraction conditions including ultrasonic power, ultrasonic time and liquid-to-solid ratio. Furthermore, their physicochemical structures, antioxidant and liver protective activity were investigated and compared. Results revealed that the functional groups and monosaccharide compositions of these grape polysaccharides collected from different varieties were similar. Nevertheless, their molecular weights, molar ratios of monosaccharide compositions and surface morphological features were different. And the antioxidant activities of these polysaccharides were screened by free radical scavenging test. 'Beichun' (BC) and 'Benni fuji' (BF) polysaccharides possessed better antioxidant function. Further, the in vivo evaluation indicated that the polysaccharides of BC and BF have a protective effect against myocardial I/R injury in mice by inhibiting myocardial necroptosis mediated by mitochondrial ROS generation. Therefore, BC and BF grapes have potential applications in the medical and food industries.